Prevention of surgical site infections in orthopaedics - Słowik, Róża; Wałaszek, Marta; Kołpa, Małgorzata (Nursing Problems / Problemy Pielęgniarstwa, 2021)
Surgical site infections (SSI) are some of the most serious postoperative complications. Orthopaedic surgery involves a higher risk of developing SSI due to inserting implants into bones that have a very sensitive structure and a good blood supply. The ability to identify and classify SSI contributes to prompt treatment and better prognosis. Prevention of SSI encompassing preoperative, intraoperative, and postoperative periods should result in the optimal health condition of the patient prior to surgery, and professional preparation of the treatment team and the environment during the operation and postoperative care. This study is a review of global guidelines concerning the prevention of surgical site infections, with particular emphasis on orthopaedics and traumatology.